Some New Synonymy in the Haemogamasidae, Laelaptidae and Diplogyniidae Indicated by an Examination of Banks' Types of Mesostigmata (Acarina) - Donald E. Johnston (Psyche: A Journal of Entomology)
During the course of a study of certain of the Banks mite types in the collection of the Museum of Comparative Zoology at Harvard College some cases of obvious synonymy were found. Two of these cases sink Banks’ names; the remainder result in the establishment of his names as senior synonyms. In addition to those of Banks, the types of Ewing’s, Furman’s and Hicks’ species (all in U.S. National Museum) were examined in connection with this work. I am grateful to Drs. H. W. Levi and W. L. Brown for arranging for me to study the Harvard collection and for their many kindnesses during my visit. The following lectotype designations are not as precise as one would wish. The Banks types in the Museum of Comparative Zoology are not numbered and most names are represented by cotypes. All of the suspected and certain type slides are arranged alphabetically according to species and kept as a unit in the Arachnida collection of the Museum. Thus the lectotypes designated herein will be found labeled as such in their proper place in the alphabetical filing scheme. It may also be noted here that some of Banks’ species (none of those treated herein) are represented by cotypes in both the MCZ and the Acarina collection of the U.S. National Museum. The same is true of Jacot’s material which has been divided evenly between these museums.